2022
DOI: 10.1002/prp2.953
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety in home care: A multicenter cross‐sectional study about medication errors and medication management of nurses

Abstract: Studies assume that up to 30% of home care recipients are exposed to a possible medication error. For the home care sector, the study situation regarding such errors is limited. The aim of the study was to find out how often medication errors occur and whether they are related to training, quality assurance measures (use of the double‐check principle (DCP)), and other structural conditions of home care services. A cross‐sectional study was conducted, comprising 485 fully trained nurses of 107 randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Several cross-sectional studies have demonstrated that regular error management training significantly reduces the incidence of home-based nursing and medication-related errors, thereby contributing to enhanced patient safety. 29 , 30 Also, Japanese scholars Morioka et al discovered a favored association between training opportunities and the number of nurses within the home-visit nursing agencies, 31 thereby contributing to increased workforce staffing. Researchers Larsson et al identified a positive relationship between the self-efficacy of home care nurses and the secure work environment, as evidenced by their investigation earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies have demonstrated that regular error management training significantly reduces the incidence of home-based nursing and medication-related errors, thereby contributing to enhanced patient safety. 29 , 30 Also, Japanese scholars Morioka et al discovered a favored association between training opportunities and the number of nurses within the home-visit nursing agencies, 31 thereby contributing to increased workforce staffing. Researchers Larsson et al identified a positive relationship between the self-efficacy of home care nurses and the secure work environment, as evidenced by their investigation earlier.…”
Section: Discussionmentioning
confidence: 99%